The Impact of Administrative Governance on the Development of Institutional Organization within Libyan Universities: A Field Study at Sebha University (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze the relationship between administrative governance and organizational structure at Sebha University, and to examine the impact of governance principles on enhancing organizational efficiency and improving institutional performance. The study adopted the descriptive-analytical and correlational approaches, using a questionnaire as the main data collection tool from a sample of (140) faculty and administrative staff members.The findings revealed that both administrative governance and organizational structure were at a moderate level, indicating the need for further improvement in administrative practices within the university. The results also showed a strong positive and statistically significant correlation between administrative governance and organizational structure (r = 0.78). In addition, regression analysis indicated a significant effect of administrative governance on organizational structure. The study concluded that the relationship between the two variables is integrative and contributes to enhancing institutional performance.
Keywords: Administrative Governance, Organizational Structure, Sebha University, Institutional Performance, Higher Education, Administrative Transparency, Accountability, Organizational Efficiency, University Management, Statistical Analysis.